Śląsk nieoczywisty – literacki obraz górnośląskiego krajobrazu w Kajś. Opowieści o Górnym Śląsku Zbigniewa Rokity - Płonka, Karolina (Przestrzenie Teorii, 2025)
The article is dedicated to an analysis of the Upper Silesian landscape, which becomes, for the author of Kajś. Opowieść o Górnym Śląsku, one of the elements that shaped his – previously lost – Silesian identity. Zbigniew Rokita’s mission, which he undertakes in his reportage, is to ‘disenchant’ the stereotypical image of industrial Silesia. The primary aim of this article is therefore to show how the reporter builds his narrative in order to achieve his goal. The analysis focuses primarily on those places on the map of Upper Silesia that Rokita uses to build the titular unobvious image of the region. These are: Hałda Szarlota, the image of which is constructed in opposition to St. Anne’s Mountain, Bytom as a symbol of Polish colonialism in Silesia, and Camp Zgoda as one of Upper Silesia’s ‘non-places of memory’. The article also discusses the role of the media’s exclusive focus on the industrial part of Upper Silesia, while completely ignoring its agricultural, and incidentally older, part.